Cellular angiofibroma of the vulva: a poorly known entity, a case report and literature review. Issue 1 (December 2016) - Khmou, Mouna; Lamalmi, Najat; Malihy, Abderrahmane; Rouas, Lamia; Alhamany, Zaitouna
Abstract Background Cellular angiofibroma represents a newly described, site specific tumor. Histologically, CAF is a benign mesenchymal neoplasm characterized by two principal components: bland spindle cells and prominent small to medium-sized vessels with mural hyalinization. The indolent nature of the lesion is underscored by the uniformity of its constituent stromal cells, and their lack of nuclear atypia. Characterization by immunohistochemistry is helpful distinguishing Cellular angiofibroma from other mesenchymal lesions. Case presentation We report the case of a 37-year-old woman, presenting with a painless nodule involving the vulva. This lesion had gradually increased in size; a simple excision was performed, and follow up was unremarkable. Gross examination showed a well circumscribed, firm tumor measuring 3× 3 × 2, 5 cm. Histologically, the tumor was composed of uniform, short spindle-shaped cells, proliferating in an edematous to fibrous stroma and numerous small to medium-sized thick-walled vessels. A panel of immunohistochemical stains was performed, and confirmed the diagnosis of Cellular angiofibroma. Conclusion In this report we aim to describe the clinical, pathological and immunohistochemical features of this rare entity through a literature review, and to discuss other vulvar mesenchymal lesions.